Advanced bipolar membranes incorporating Ti3CNTx MXene for improved BMED efficiency - Celik, Aytekin; Yegin, Mustafa; Kose, Yusuf; Hasar, Halil (Springer, 2025)
In this study, titanium carbide nitride MXene, Ti3CNTx, was synthesized using two distinct etching methods: direct hydrofluoric acid and a combination of lithium fluoride and hydrochloric acid. The synthesized material was incorporated into bipolar membranes to enhance their performance in bipolar membrane electrodialysis. The titanium aluminum carbonitride precursor, Ti3AlCN, was etched to obtain few-layered Ti3CNTx, as confirmed by a shift in the (002) peak in X-ray diffraction patterns and the disappearance of the aluminum 2p signal in X-ray photoelectron spectroscopy. Scanning electron microscopy revealed greater delamination at elevated temperatures, particularly for samples etched with hydrofluoric acid at 40 degrees C. Thermogravimetric analysis indicated that delaminated MXene exhibited reduced thermal stability. Bipolar membranes were fabricated using sulfonated polysulfone as the cation exchange layer and aminated chloromethylated polysulfone as the anion exchange layer, with Ti3CNTx incorporated at loadings of 0.1 and 0.3 g. Fourier-transform infrared spectroscopy confirmed successful chemical modification. Contact angle measurements and water uptake analysis showed that MXene derived from hydrofluoric acid improved hydrophilicity more effectively than that derived from lithium fluoride and hydrochloric acid. Mechanical testing demonstrated that the Young's modulus increased from approximately 600 MPa in the control membrane to approximately 1100 MPa in the membrane containing 0.3 g of hydrofluoric acid-derived MXene. Electrodialysis experiments conducted with a 0.5 molar sodium chloride solution demonstrated enhanced proton and hydroxide ion generation in membranes containing 0.3 g of MXene. The membrane with hydrofluoric acid-derived MXene reached peak logarithmic hydrogen ion concentration values of approximately 4.6 and hydroxide ion values of approximately 2.85, while the membrane with lithium fluoride and hydrochloric acid-derived MXene achieved values of approximately 3.6 and 3.5, respectively. When tested with reverse osmosis concentrate containing 0.6 molar sodium chloride, membranes incorporating MXene synthesized with lithium fluoride and hydrochloric acid produced more stable ion concentrations. Post-electrodialysis analysis using scanning electron microscopy with energy-dispersive X-ray spectroscopy showed reduced membrane fouling and increased oxygen and sulfur content in MXene-containing membranes, particularly in those with hydrofluoric acid-derived MXene. These findings demonstrated that titanium carbide nitride MXene, especially when synthesized via lithium fluoride and hydrochloric acid etching, enhanced membrane hydrophilicity, mechanical strength, and electrodialysis performance, thereby supporting sustainable acid and base generation from saline wastewater.
Keywords: Ti3CNTx MXene; Bipolar membrane electrodialysis; HF and LiF plus HCl etching; Water splitting; RO concentrate